Estrogen-receptor independent effects of two ubiquitous environmental estrogens on Melosira varians Agardh, a common component of the aquatic primary production community - Julius, Matthew L.; Stepanek, Joshua; Tedrow, O’Neill; Gamble, Carolyn; Schoenfuss, Heiko L. (Aquatic toxicology, 2007)
Estrogenic compounds have been discovered in many surface water samples in many anthropogenically altered surface waters. Wastewater effluent has been identified as a major pathway of contamination and found to revert much of the metabolic products of these biologically active compounds back to their original form. This presentation explains methodology for determining exposure effects through a newly developed bioassay, examining the physiological response of a diatom to these compounds. Diatoms represent an important aspect of the primary production community. They are a desirable food source over other members of the primary production community through storage of photosynthetically produced sugars in the form of lipids rather than starch. Therefore, many members of higher trophic levels selectively feed on diatoms when present with other members of the primary production community. This study examines the effects of 17β-estradiol and 4-nonylphenol on the physiological development of the diatom species Melosira varians. Clearly, unicellular protists such as diatoms are not susceptible to these contaminants in a manner directly analogous to that expressed in vertebrates. However, estradiol and nonylphenol are lipophilic making them particularly effective in entering the diatom cell membrane. Melosira varians was selected because it commonly occurs in most freshwater environments and has been the subject of other toxicological studies. An adequate literature base also exists for evaluating results of this experiment. The species grows rapidly and is easy to maintain in culture. Comparing cell density, chl- a, and lipid content in control and exposed cultures allowed interpretation of how the species responded to varying compound concentrations. Results of this study revealed differences in responses to each compound. 17β-estradiol appears to have no detrimental effect on M. varians, while 4-nonylphenol results in cell mortality with sufficient dosage. Similar results with 17β-estradiol are reported for other autotrophic organism, but the 4-nonylphenol response is not as uniform in other photosynthetic groups. The use of a phytoplankton species as a test organism complements other investigations involving vertebrate models at or near the apex of the trophic hierarchy by considering effects at the base of the food web.